Adult Osteomyelitis in a Developing Community (Global Journal of Medical Research, 2017)
Osteomyelitis, which means bone marrow inflammation, has been known since antiquity. However, it is still a current challenge. Accordingly, its epidemiology has been studied worldwide. For example, from USA has come a case series. In like manner, the present series comes from a developing community consisting of the Ibos or Igbos, an ethnic group domiciled mostly in South-eastern Nigeria. The study was stimulated by the affirmation of a Birmingham (UK) group that the establishment of a histopathology data pool facilitates epidemiological analysis. The present pool is a Reference Pathology Laboratory. It was striking that, among the 24 patients documented, the males were more often involved than females. Other parameters featured singly such as that the 3rd Decade was the commonest for both sexes.
Keywords: bone; inflammation; osteomyelitis; epidemiology; developing community